A survey of the ratio of the mesiodistal crown diameters of the permanent maxillary central incisors, lateral incisors and canines of UPCD students, schoolyear 1993-1994 - Santos, Ma. Bella Aurora D.
A survey was conducted to determine the mesiod istal crown diameters of maxillary central incisors, lateral incisors and canines of UPCD students of schoolyear 1993-94. The significance of this survey is to aid in pontic selection and fabrication in prosthodont ics and to analyze space discrepancies in orthodontics. The subjects consisted of 63 students, 47 females and 18 males, whose ages range from 19-22 years. Impressions of the upper arch were taken and casts were poured in stone. The mesiodistal diameter of each upper anterior tooth was then measured using a boley gauge which is accurate up to 0.1 mm. The mean values of the central incisors, lateral incisors and canines were then computed and statistically analyzed to derive the mean ratio of the said teeth. Based on the data gathered, the calculated mean ratio for males and females are 1.25 : 1 : 1.14 and 1.28 : 1 : 1.15 respectively. A model was also derived which can be used to predict the size of unerupted teeth.